PENGARUH PEMBERIAN AIR KELAPA HIJAU TERHADAP PENURUNAN SKALA DISMENOREA PADA REMAJA - Metha Fahriani; Elza Wulandari; Buyung Keraman; Mia Roza Mentari (Universitas Pahlawan, 2022)
Women in Indonesia 90% have experienced menstrual pain, based on a survey of numbers primary dysmenorrhea at Junior High School Number 003 Arga Makmur North Bengkulu from 136 students as many as 20 15% of cases experienced dysmenorrhea. Dysmenorrhea is abdominal pain that comes from uterine cramps and occurs during menstruation. The research aims to find out whether there are the effect of green coconut water on reducing menstrual pain (dysmenorrhea) and knowing the average menstrual pain (dysmenorrhea) before and after the intervention. Research design used is a pre-experimental design with the one group pretest and posttestwhich was carried out on July 1 to July 30, 2022. The instrument used NumericRating Scale with data analysis techniques Normality Test, Univariate Test, and Bivariate. Based on the results of the study where before the intervention the average respondent (20 people) experiencing severe pain 7.85 and after the intervention as much as 250 ml of green coconut water 2 times a day for 3 days during menstruation, the average respondents (20 people) were is moderate pain 4.7 A total of 18 respondents experienced a decrease in pain scale, and 2 respondents the pain scale is fixed. From the results of the Wilcoxon test, the p-value = 0.000 <0.05 is significant, then Ho is rejected and Ha is accepted. In conclusion, there is an effect of giving green coconut water on reducing dysmenorrhea in adolescents at SMPN 003 Arga Makmur North Bengkulu in 2022 It is hoped that the results of this study can be an alternative for the school in dealing with students who experience primary dysmenorrhea.